The Didactic, Pedagogic Thinking of Juan Amós Comenio: His Role in the Pansofia Triadic - Andrés Klaus Runge Peña (Universidad Pedagógica Nacional, 2013)
This article shows the role that conceptions of didactics and pedagogy achieve inside the Comenio´s triadic pansophia. So, such conceptions make part of a wider philosophy thought called 'pansophia'. The pansophia, as a diagnosis against the process of deterioration and lack of organization of the world, leads towards a pampedia as a remedy and therapy for this evil. The universal reform of the humanity proposed by Comenio has to do with a universal education, in which pedagogy and didactics find their justification.